Slope stability analysis using Universal Distinct Element Code (UDEC) method - Roslan R.; Omar R.C.; Putri R.F.; Wahab W.A.; Baharuddin I.N.Z.; Jaafar R. (Institute of Physics Publishing, 2023)
Dynamic loads; Environmental management; Rock mechanics; Rocks; Slope protection; Stress analysis; Discontinuum; Dynamic loadings; Jointed rock mass; Rock mass; Slope stability analysis; Stress wave; Universal distinct element codes; Slope stability